Observasi Gaya Kepemimpinan Terhadap Kinerja Pekerja Pada Proyek Preservasi Rekonstruksi Jalan Surabaya-Gresik-Sadang - Totok Dwi Sutanto; Sugeng Dwi Hartantyo (Universitas Negeri Gorontalo, 2020)
Leadership style within the company or in the project location greatly influences the work progress. The use of improper leadership style would influence the execution of the project, which would have a negative impact on the success of the project. This study aims to determine the influence of leadership style by using several indicators of leadership style, namely traits, temperament, habits, character and personality. The analytical method used in this study is the validity test, reliability test, determination test (R) and t-test. The data was obtained using questionnaires distributed at the research location. The results of the study indicated that the validity test and the reliability test was shown to be valid and reliable, an error rate of 95% or 0.05 resulted in the determination test results, which produced 88% of the variable variation in employee performance which can be explained by leadership style variables. While the t-test yielded the results of X1 = 2,71, X2 = 3,230, X3 = 4,278, X4 = 7,217 and X5 = 3,253, all of which are significant. Based on the results of the test, it can be interpreted that the leadership style has a significant and positive influence on performance.